Beyond Traditional Sunscreens: A Review of Liposomal-Based Systems for Photoprotection - Júlio Abreu Miranda; Yasmin Ferreira da Cruz; Ícaro Chaves Girão; Fabia Julliana Jorge de Souza; Wógenes Nunes de Oliveira; Éverton do Nascimento Alencar; Lucas Amaral-Machado; Eryvaldo Sócrates Tabosa do Egito (MDPI AG, 2024)
Sunscreen products are essential for shielding the skin from ultraviolet (UV) radiation, a leading cause of skin cancer. While existing products serve this purpose, there is a growing need to enhance their efficacy while minimizing potential systemic absorption of UV filters and associated toxicological risks. Liposomal-based formulations have emerged as a promising approach to address these challenges and develop advanced photoprotective products. These vesicular systems offer versatility in carrying both hydrophilic and lipophilic UV filters, enabling the creation of broad-spectrum sunscreens. Moreover, their composition based on phospholipids, resembling that of the stratum corneum, facilitates adherence to the skin's surface layers, thereby improving photoprotective efficacy. The research discussed in this review underscores the significant advantages of liposomes in photoprotection, including their ability to limit the systemic absorption of UV filters, enhance formulation stability, and augment photoprotective effects. However, despite these benefits, there remains a notable gap between the potential of liposomal systems and their utilization in sunscreen development. Consequently, this review emphasizes the importance of leveraging liposomes and related vesicular systems as innovative tools for crafting novel and more efficient photoprotective formulations.